THE EFFECT OF INVESTMENT DECISIONS, CAPITAL INTENSITY, POLLITICAL CONNECTION AND CAPITAL STRUCTURE ON FIRM VALUE IN PUBLIC STATE-OWNED COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2019-2022 - Sri Handayani; Nirwana, Nihlatul Qudus Sukma (Journal of Economic and Economic Policy, 2025)
Objective: This study aims to determine the Influence of Investment Decisions, Capital Intensity, Political Connection and Capital Structure on Company Value in State-Owned Enterprises Listed on the Indonesia Stock Exchange in 2019-2022. Method: This research is a type of quantitative research. The sampling method used is the purposive sampling method. The number of companies sampled in this study is 23 State-Owned Enterprises Listed on the Indonesia Stock Exchange in 2019-2022. The data source used is secondary data. The data analysis method used in this study is Multiple Linear Regression with SPSS version 27 data processing tools. Results: The results of this study indicate that Investment Decisions Affect Company Value. Capital Intensity Affects Firm Value. Political Connection Affects Firm Value. Capital Structure Affects Firm Value. Novelty: This study provides new insights by simultaneously examining the effect of Investment Decisions, Capital Intensity, Political Connection, and Capital Structure on Company Value specifically in State-Owned Enterprises listed on the Indonesia Stock Exchange during the 2019–2022 period, which has not been comprehensively explored in previous studies.